2010
DOI: 10.1093/ntr/ntq198
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Increases Choice of Cigarettes Over Money

Abstract: The results of this study suggest that methylphenidate increases the relative reinforcing efficacy of cigarette smoking. Stimulant use may thus be an important consideration for individuals attempting to quit smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…If a subject chose only money, choices would have been between a cigarette and US$0.25, 0.50, 0.75, 1.00, 1.25 and 1.50, as was the case for the Escalating Condition. The money values were selected based on previously published research (Bisaga et al, 2007; Stoops et al, 2011; Tidey et al, 2000). Subjects were provided with detailed instructions about the money values available at the beginning of each session.…”
Section: Methodsmentioning
confidence: 99%
“…If a subject chose only money, choices would have been between a cigarette and US$0.25, 0.50, 0.75, 1.00, 1.25 and 1.50, as was the case for the Escalating Condition. The money values were selected based on previously published research (Bisaga et al, 2007; Stoops et al, 2011; Tidey et al, 2000). Subjects were provided with detailed instructions about the money values available at the beginning of each session.…”
Section: Methodsmentioning
confidence: 99%
“…In all studies, at least one dose of methylphenidate increased the total number of puffs significantly compared to placebo (Rush et al 2005; Vansickel et al 2007, 2009). In another study from our laboratory, methylphenidate was shown to increase the choice of cigarettes over money (Stoops et al 2011). Participants in that study were administered methylphenidate (0, 10, 20, and 40 mg) and then made a series of choices between half of a cigarette and US $0.25.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reporting increases in smoking behavior following stimulant drug administration have examined ad libitium smoking (i.e., with no response requirements; Cousins et al, 2001; Rush et al, 2005), a PR task with only a single alternative available (Sigmon et al, 2003), or a choice procedure in which participants made discrete choices for cigarette puffs or money (Stoops et al, 2011; Tidey et al, 2000). It is important to note that in both of the studies using discrete choices for cigarettes versus money, the value of the cash option was lower than that used in the present study ($0.25 vs. $0.50; Stoops et al, 2011; Tidey et al, 2000), though neither of those studies examined smokers with ADHD. It may be that the use of a higher monetary reinforcer in the present study muted the effects of methylphenidate on smoking-reinforced responding.…”
Section: Discussionmentioning
confidence: 99%